The Mentoring for Teachers at Primary School 1 Jati Wetan in Developing the E-Diagnostic Assessment Model based on Literacy to Manage Learning Loss of the Learners - Fakhriyah, Fina; Masfuah, Siti; Ari Pratiwi, Ika; Hilyana, F. Shoufika (Amalee: Indonesian Journal of Community Research and Engagement, 2024)
The implementation of online learning has an unfavorable influence on students' motivation and enthusiasm for learning. So far, assessments have been carried out, but teachers at SD 1 Jati Wetan have never carried out an evaluation with e-diagnostic assessments. Community Service Activities aim to provide knowledge sharing and application of technology in order to improve teacher competence and skills by developing e-diagnostic assessments to overcome student learning loss and improve the quality of post-pandemic learning. Teachers are able to compile literacy-based e-diagnostic assessments with optimal application of technology. This activity is carried out in stages; 1) planning stage, (2) socialization and training stage for introducing literacy-based e-diagnostic assessments, (3) training and assistance stage for designing literacy-based e-diagnostic assessments, (4) technology application stage, (5) e-implementation stage literacy-based diagnostic assessment to identify learning loss, and (6) evaluation stage of program activities and sustainability. The results of Community Service activities are in the form of developing literacy-based e-diagnostic assessments and being skilled in their application to identify learning loss. Literacy-based diagnostic assessment products are implemented programmatically and productively by teachers.